Brazil : Forging a Strategic Partnership for Results, An OED Evaluation of World Bank Assistance - Operations Evaluation Department (Washington, DC: World Bank, 2013)
Brazil entered the 1990s suffering the consequences of a lost decade of high inflation and slow growth. Between 1980 and 1990, per capita income declined in real terms, and the share of the population in extreme poverty rose from 16.5 to 19 percent -and from 36 to 42 percent in the Northeast. Income distribution worsened. Key social indicators improved little, particularly in the Northeast. These adverse conditions persisted in the early 1990s because the government failed to stabilize the economy and to articulate a development agenda. Conditions improved only with the success of the 1994 Real Plan. Stabilization contributed to a decline in poverty and enabled the government to articulate a development agenda with clear goals for education and other sectors during the remainder of the 1990s.